Investigations of an annulation-fragmentation-spirocyclisation approach to fawcettimine-type Lycopodium alkaloids - Seah, KY; Robertson, J (Elsevier, 2019)
This paper reports progress in the development of a furan oxidative N-spirocyclisation approach to the fawcettimine alkaloids huperzine Q and lycopladine D. A short synthesis is described of a key intermediate cyclopentaindolizidine that subsequently fragments by N-acylation and β-elimination. The stereochemistry of 1,4-addition of cyanide to the resulting enone is discussed with supporting molecular modelling calculations. N-Deprotection is shown to be accompanied by cyclisation onto the nitrile group, resulting in a tricyclic lactam with a twisted amide functionality. Elaboration of this lactam afforded four of the five rings present in lycopladine D with just the C(8) carbon lacking.